Photoacoustic imaging of breast microcalcifications: A validation study with 3‐dimensional ex vivo data and spectrophotometric measurement. Issue 1 (2nd September 2013) - Kang, Jeeun; Kim, Eun‐kyung; Kim, Ga Ram; Yoon, Changhan; Song, Tai‐kyong; Chang, Jin Ho
<x xml:space="preserve">Abstract</x> This paper investigates whether photoacoustic imaging (PAI) can provide the visualization of microcalcifications in breast tissue. For this, the geometrical correlation between the 3‐D PA images of breast microcalcifications within ex vivo specimens and the corresponding mammograms is ascertained. Also, the optical absorbance of the calcification compositions (i.e., hydroxyapatite and calcium oxalate) is measured and compared with the PA responses of the microcalcifications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>